On the Influence of the Protonation States of Active Site Residues on AChE Reactivation: A QM/MM Approach. (23rd February 2017) - Driant, Thomas; Nachon, Florian; Ollivier, Cyril; Renard, Pierre‐Yves; Derat, Etienne
Abstract: Acetylcholinesterase (AChE), an enzyme of the serine hydrolase superfamily, is a mediator of signal transmission at cholinergic synapses by catalyzing acetylcholine cleavage into acetate and choline. This enzyme is vulnerable to covalent inhibition by organophosphate compounds (like VX). Covalent inhibition of AChE does not revert spontaneously. Known reactivator compounds have limited action in restoring catalytic activity. QM/MM simulations of VX‐inhibited AChE reactivation by pralidoxime (2‐PAM), a classical reactivator, were performed. These afforded a broad view of the effect of protonation states of active‐site residues, and provide evidence for the role of Glu202, which needs to be protonated for reactivation to occur. In situ deprotonation of 2‐PAM for both protonation states of Glu202 showed that His447 is able to deprotonate 2‐PAM with the assistance of Glu202. Because the active site of serine hydrolases is highly conserved, this work provides new insights on the interplay between the catalytic triad residues and this glutamate, newly identified as protonatable. Abstract : Proton transfer during reactivation of organophosphate‐inhibited acetylcholinesterase was investigated by QM/MM calculations. These revealed an interplay between protonation states of the catalytic triad and a glutamate close to the active site; these need to be protonated for reactivation to occur.